PROBLEMATIKA GURU DALAM MEMBERIKAN PENGUATAN (REINFORCEMENT) MATA PELAJARAN PAI DI MTs AL-ANWAR SANAH TENGAH WARU PAMEKASAN - Supandi Supandi (Universitas Islam Madura, 2018)
The subject of the study in this study are: 1) The form of the problems caused in providing maple PAI reinforcement conducted by the teacher, 2) How to overcome the problems faced by the teacher in providing PAI map reinforcement. This study uses a qualitative approach, with a type of descriptive data analysis. This data collection is obtained through interviews, observation and documentation analysis. The informants from this study were principals, teachers and some students in the research location. The technique used to check data credibility is the extension of the presence of researchers and in-depth observation and triagulation. The results show that the problems caused in providing reinforcement are a) learning methods that are considered less varied by the teachers, b) learning media that are considered to be less qualified, c) internal and external factors of students which are the problems of PBM's success, d) Uneven human and natural resource problems. Whereas ways to overcome these problems include: a) including MGMP program teachers, b) Making maximum use of learning media, c) Conducting good communication networks for all parties, d) Pairing between the smart and the less intelligent.